Legal Certainty of Music Royalties in Commercial Public Spaces: Constitutional Court Decision No. 28/PUU-XXIII/2025 - Muhammad Dwi Sakti Rahim; Dolot Alhasni Bakung; Nurul Fazri Elfikri (Nusantara: Journal of Law and Islamic Law, 2026)
Ambiguous stipulations in the Indonesian Copyright Law regarding royalty liabilities have historically disadvantaged performing artists through double claiming. This normative legal research examines Constitutional Court Decision 28/PUU-XXIII/2025 utilizing statutory, conceptual, and case approaches to evaluate its profound impact on music royalty governance. The analysis demonstrates that the ruling decisively resolves normative uncertainty by attributing strict royalty liability directly to commercial event organizers, simultaneously mandating objective statutory tariff standardization. Nevertheless, the discussion reveals persistent structural impediments concerning post-ruling implementation within the creative economy. These cPagelenges encompass low legal compliance among commercial users due to inadequate socialization, jurisdictional dualism between national and sectoral collective management organizations, and profound transparency deficits within the digital music information system. Consequently, while this landmark judicial intervention successfully restores normative legal certainty and protects creators' fundamental economic rights, realizing substantive justice necessitates comprehensive administrative harmonization, advanced digital transparency, and sustained legal education to foster optimal industry compliance.